Dinamika Ekosistem Bisnis Halal dan Perlindungan Konsumen: Analisis Implikasi Fatwa MUI No.83 Tahun 2023 - Sulthon Muhammad Yusuf J; Yudi Wahyudin; Desi Cahya Anggraeni; Syahrial Syahrial; Syifa Febriana Nurul Wildain (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines the implications of MUI Fatwa No. 83 of 2023 on the halal business ecosystem and Muslim consumer protection in Indonesia. The fatwa, which contains a call to boycott Israel-affiliated products, has created new dynamics in the halal business ecosystem that transcend purely religious dimensions and fundamentally touch upon economic, legal, and consumer protection aspects. This study employs a normative legal method with statutory, conceptual, and case approaches, through a literature study of relevant primary, secondary, and tertiary legal materials. The results reveal three main findings: first, MUI Fatwa No. 83 of 2023 holds a legal position as an Islamic legal instrument that is morally-religiously and sociologically binding, established through a collective ijtihad mechanism grounded in maqashid al-syariah; second, the fatwa creates multidimensional implications for the halal business ecosystem, including shifts in Muslim consumer preferences, declining revenues of affected multinational corporations, the emergence of digital-based cancel culture phenomena, while simultaneously opening strategic opportunities for local halal industry development; third, the fatwa provides multidimensional legal protection for Muslim consumers, complementing existing positive legal instruments namely Law No. 8 of 1999 and Law No. 33 of 2014, yet requires immediate regulatory harmonization to avoid legal uncertainty within the national halal certification ecosystem. This study recommends harmonization between Fatwa No. 83 of 2023 and the halal certification regulatory framework, strengthening digital halal information systems, and enhancing the capacity of local halal MSMEs.